The impact of metal amino acid complexes on cuticle quality and Salmonella Enteritidis contamination in laying hens’ eggs - Clemente, Saruanna M. S.; Barros, Mércia R.; Rabello, Carlos B. V.; Santos, Marcos Jose Batista dos; Medeiros-Ventura, Waleska R. L.; da Silva Junior, Rogério Ventura; Melo, Felipe P.; Silva, Priscila O.; Santos, Fábio A. B.; Burin, Raquel; Fireman, Alba (Frontiers in Veterinary Science, 2026)
IntroducionEggshell quality and microbial safety are critical concerns in poultry production, with Salmonella Enteritidis contamination representing a significant public health risk. Traditional inorganic mineral supplementation may not optimize eggshell integrity against bacterial penetration. This study investigated the effects of different metal–amino acid complexes on eggshell cuticle quality and resistance to S. Enteritidis penetration in egg laying hens.Material and methodsTwo experiments were conducted with 67-week-old Dekalb White laying hens with treatments consisting of inorganic minerals (IM; Control at 100% recommendations inclusion) or different trace mineral inclusion rates (100, 70, and 40%) as either amino acid-complexed minerals (AACM, Experiment 1) or lysine and glutamic acid-complexed minerals (LGCM, Experiment 2). The quality of the eggshell cuticle was measured using spectrophotometric analysis, and experimental contamination with S. enteritidis was performed to evaluate bacterial penetration after various storage periods.ResultsSupplementation with 40% AACM improved shell thickness and palisade layer values compared to IM (p < 0.01). LGCM supplementation at 70 and 40% levels enhanced cuticle visual staining scoring (p < 0.01). Eggs from hens fed 40% AACM reduced Salmonella contamination, with 91.7% of samples classified as having no risk for consumption. All LGCM treatments completely prevented S. Enteritidis penetration into egg yolks regardless of inclusion level. In conclusion, AACM improved eggshell quality and reduced S. Enteritidis contamination in eggs.ConclusionSupplementation with 40% AACM resulted in 91.7% of samples being free of yolk contamination, while LGCM supplementation at all levels completely prevented bacterial penetration into egg yolks, achieving 100% safety despite eggshell contamination.